Evaluation of cardiometabolic risk factors in women with breast cancer before and after chemotherapy with doxorubicin and cyclophosphamide - T. A. Brodskaya; T. S. Satalkina; B. I. Geltser; V. N. Kotelnikov (Российский кардиологический журнал)
Aim. To evaluate cardiometabolic risk (CMR) factors in women with breast cancer (BC) before and after chemotherapy (CT) with doxorubicin and cyclophosphamide.Material and methods. This prospective cohort study included 154 women with a median age of 43 years with newly diagnosed stage IIA-IIIB BC. Three following groups were identified among the examined women: with normal blood pressure (BP), masked hypertension (MH) and primary hypertension (HTN). All patients after BC surgery underwent 4 courses of chemotherapy with doxorubicin and cyclophosphamide lasting about 3 months. The assessment of CMR factors was carried out at 3 following stages: I — before chemotherapy; II and III — 7-14 days and 90-120 days after its completion. Fasting blood glucose, total cholesterol (TC), triglycerides (TGs), high-density (HDL-C) and low-density lipoprotein cholesterol (LDL-C), and non-HDL-C were determined. The atherogenicity coefficient, visceral obesity index (VAI) and lipid accumulation product (LAP) index were calculated.Results. In women with comorbidity of BC and HTN, the body mass index (BMI) decreased at stage II and returned to the initial level at stage III, while class I obesity was recorded in almost a third of patients. In the MH group, an increase in BMI was observed 90-120 days after the end of chemotherapy. In patients with normal BP, TC level did not change significantly during the follow-up, and among women with HTN, a significant increase in TC compared to the baseline was determined 90-120 days after the completion of chemotherapy. In patients with comorbidity of BC and HTN at stage III, the highest concentration of LDL-C, non-HDL-C and the lowest concentration of HDL-C in the blood were established, which distinguished them from individuals with normotension and MH. Hypertriglyceridemia was recorded in most patients with MH and hypertension after the completion of chemotherapy. The median values of TGs, VAI and LAP index in individuals with normal BP were significantly lower than in the comparison groups at all stages.Conclusion. In patients with BC after adjuvant chemotherapy with doxorubicin and cyclophosphamide, an increase in the level of atherogenic lipids and visceral obesity indicators is recorded, which is more pronounced in the case of comorbidity of BC and HTN. Metabolic status disorders after chemotherapy persisted for up to 3-4 months, which indicates the need for long-term monitoring of changes.